PERBANDINGAN RESPON SEISMIK BALOK KAYU BIASA DENGAN KOMPOSIT BAJA RINGAN SEBAGAI KOMPONEN STRUKTUR RUMAH TAHAN GEMPA: Penelitian dinamika struktur - Pinondang Simanjuntak (UKI Press, 2021)
abstract Indonesia is one of the areas that are at risk of earthquakes. According to the world earthquake map, Indonesia is located on an area line that is always shaken by earthquakes. The area line is referred to by geologists as